Physical and Chemical Investigation of TiO2Nanotubes Treated with Isopropyl Triisostearoyl Titanate (KR-TTS) - Sabri B.A.; Satgunam M.; Manap A.; Gnanasagaran C.L.; Ramachandran K. (Hindawi Limited, 2024)
The aim of this study is to investigate the effect of isopropyl triisostearoyl titanate (KR-TTS) as a titanate coupling agent (TCA) on surface modification of TiO2 nanotube (TNT) material. From the physical and chemical studies that have been performed on the modified TiO2 nanotube, scanning electron microscope micrographs, energy-dispersive X-ray and viscosity indicated that there was significant reduction in particle aggregation of the modified TiO2 Nanotube. FTIR spectroscopy confirmed that the functional group of the TCA reacted with the hydroxyl groups present on the surface of TiO2 nanotube resulting in an altered surface property from being hydrophilic to hydrophobic. X-ray diffraction indicated that crystalline structure did not change upon the modification with the coupling agent. Isopropyl triisostearoyl titanate (KR-TTS) is found to be superior in performance and has a significant effect on the dispersion and resolving of agglomeration. This paper presents the effect of surface modification with the TCA of isopropyl triisostearoyl titanate (KR-TTS) type on the TiO2 nanotube material. 2023 Ban Ali Sabri et al.